Review of Factors Affecting Egg Quality and Its Effect - Abebe, Fanta; Mulatu, Henok; Kelemework, Samuel (Journal of Animal Health, 2023)
Purpose: Global commercial egg production, it is estimated that over 75% of hens are reared in cages but trends are emerging for maintaining layers in animal-friendly systems. The alternative systems have focused on developing better animal welfare and behaviour for laying hens. Methodology: The study adopted desktop literature review. Findings: Egg quality is an important factor influencing consumer purchase of eggs eggshell quality is one of the critical factors affecting overall egg quality before and after harvest. The quality of eggs is affected by some factors of both internal (genetic influences, age of the hen, laying cycle stage) and external nature, such as the nutritional level, microclimate parameters, and the system of management and housing system selected is economically important and also eggs are used in many food preparations and many industries the effect of some of these factors such as disease has been known for a long time while other factors such as certain drugs have been studied only in the past year or two. Certain drugs serve a very useful purpose when used for the purpose for which they were intended but when inadvertently fed to laying chickens may have disastrous effects. Unique Contribution to Theory, Practice and Policy: promoting awareness to producers, consumers, and food processing industries to Ensure Food Safety of Eggs by applying proper hygiene practices in egg production and processing. Food poisoning special care is needed with handling and preparing fresh eggs or egg products; frozen, liquid, or dried egg products for consumption.